Optimalisasi Pembelajaran Kebencanaan Dengan Media Belajar Berbasis Teknologi Digital Untuk Membentuk Generasi Tangguh Bencana - Siti Muslikhah; Suwarno Suwarno (UM Purwokerto Press, 2022)
Natural disasters are events that have the potential to occur in all regions in Indonesia. The consequences of natural disasters for example loss of property and the high number of casualties due to the weak generation of resilience to a disaster. The disaster-resilient generation is not formed directly in students but must go through a long educational process. optimization of disaster learning and technology-based learning media to form a disaster-resilient generation is the most appropriate step in strengthening the disaster-resilient generation of students. Optimization of disaster learning is a very important thing to be held from elementary to university levels. This study aims to find out conceptually-theoretically how to optimize disaster learning and technology-based learning media to form a tough generation in SMP Negeri 1 Cilacap students. The method used in this research is the library research method, or it can also be called the literature review method, which is a type of research conducted by reviewing related and relevant literature. The analysis technique in this study uses a qualitative descriptive analysis technique. Based on the results of data analysis, it can be concluded that the optimization of disaster learning and technology-based learning media can form a generation of disaster resilience in students. So that the stronger the resilient generation can reduce the risk of disasters that will occur in the community.